2004
DOI: 10.1089/1540658041410696
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assay of Voltage-Gated Sodium Channels Using Membrane Potential-Sensitive Dyes

Abstract: The discovery of novel therapeutic agents that act on voltage-gated sodium channels requires the establishment of high-capacity screening assays that can reliably measure the activity of these proteins. Fluorescence resonance energy transfer (FRET) technology using membrane potential-sensitive dyes has been shown to provide a readout of voltage-gated sodium channel activity in stably transfected cell lines. Due to the inherent rapid inactivation of sodium channels, these assays require the presence of a channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 22 publications
5
61
0
Order By: Relevance
“…In many of these cases, where voltage cannot be used to activate the channels, 12,13 small-molecule activators such as veratridine or deltamethrin are used to increase the open probability of the channel to evoke a significant response that can be detected. [14][15][16] Two membrane potential dyes are widely used for HTS: the FLIPR Membrane Potential dye (Molecular Devices, Sunnyvale, CA) that uses a fluorescence indicator in combination with a quencher and voltage sensor probes (VSPs) that rely on fluorescence-resonance energy transfer (FRET) between a voltage-sensing oxonol acceptor and a fluorescent membrane-bound coumarin dye. 17 In the current study, we compared the performance of these membrane potential dyes, along with a sodium-sensing dye, in assay development and found that these dye systems could only detect certain subsets of Na V 1.7 inhibitors using standard data analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…In many of these cases, where voltage cannot be used to activate the channels, 12,13 small-molecule activators such as veratridine or deltamethrin are used to increase the open probability of the channel to evoke a significant response that can be detected. [14][15][16] Two membrane potential dyes are widely used for HTS: the FLIPR Membrane Potential dye (Molecular Devices, Sunnyvale, CA) that uses a fluorescence indicator in combination with a quencher and voltage sensor probes (VSPs) that rely on fluorescence-resonance energy transfer (FRET) between a voltage-sensing oxonol acceptor and a fluorescent membrane-bound coumarin dye. 17 In the current study, we compared the performance of these membrane potential dyes, along with a sodium-sensing dye, in assay development and found that these dye systems could only detect certain subsets of Na V 1.7 inhibitors using standard data analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 The latter is often based on the membrane potential changes following ion fluxes. 12,13 Using surrogate ionic fluxes, several large HTS campaigns have been recently described in published reports 14,15 and in a public database (PubChem AIDs 1456, 1511, 1672, 1918, 2156, and 2239). Examples of HTS campaigns using direct measurement of ionic current have been less commonly reported.…”
mentioning
confidence: 99%
“…[137][138][139][140] The interaction of Compound 4 with Na v 1.7, Na v 1.8, and Na v 1.5 channels was further characterized in whole cell electrophysiology. Minimal block was observed when compound 4 was applied to hNa v 1.7 channels at Ϫ100 mV.…”
Section: Novel Na V 17 Blockers From Merckmentioning
confidence: 99%
“…Cell based, functional, fluorescence, or ion flux-based assays are typically the assays of choice for high throughput sodium channel screening. 137,[142][143][144][145] Although well suited to the screening of large compound collections, these assays have a number of significant limitations that may ultimately impact the probability of identifying subtype selective sodium channel blockers. For example, although accurate for the most part, assays reliant on membrane potential dyes are prone to artifacts.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation